2013
DOI: 10.1016/j.ajhg.2013.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Recessive TRAPPC11 Mutations Cause a Disease Spectrum of Limb Girdle Muscular Dystrophy and Myopathy with Movement Disorder and Intellectual Disability

Abstract: Myopathies are a clinically and etiologically heterogeneous group of disorders that can range from limb girdle muscular dystrophy (LGMD) to syndromic forms with associated features including intellectual disability. Here, we report the identification of mutations in transport protein particle complex 11 (TRAPPC11) in three individuals of a consanguineous Syrian family presenting with LGMD and in five individuals of Hutterite descent presenting with myopathy, infantile hyperkinetic movements, ataxia, and intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 37 publications
7
108
3
Order By: Relevance
“…Disturbances in these processes can have dramatic effects on cell metabolism. In contrast to our observation of LAMP1 hypoglycosylation, a previous study describing another TRAPPC11 mutation demonstrated not only a reduction in the cellular levels of LAMP1 and LAMP2, but the proteins were observed in a higher molecular size region of the gel as compared with controls, suggesting that they might have a higher degree of glycosylation 26. Taken together with these previous studies, our data suggest that the type of mutation, and not necessarily the cellular levels of TRAPPC11, can influence protein glycosylation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Disturbances in these processes can have dramatic effects on cell metabolism. In contrast to our observation of LAMP1 hypoglycosylation, a previous study describing another TRAPPC11 mutation demonstrated not only a reduction in the cellular levels of LAMP1 and LAMP2, but the proteins were observed in a higher molecular size region of the gel as compared with controls, suggesting that they might have a higher degree of glycosylation 26. Taken together with these previous studies, our data suggest that the type of mutation, and not necessarily the cellular levels of TRAPPC11, can influence protein glycosylation.…”
Section: Discussioncontrasting
confidence: 99%
“…Small amounts of full-length TRAPPC11 in the lysates from the affected individuals are consistent with the incomplete splicing defect and reduced mRNA levels of the regular splice product described above. In a previous study characterising the TRAPPC11 mutations p.G980R and p.A372_S429del, hyperglycosylation of lysosomal-associated membrane protein 1 (LAMP1) was demonstrated 26. In contrast to that study, we found that LAMP1 was hypoglycosylated in both F1.II:1 and F1.II:2 (figure 3A).…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…Exome and genome sequencing has revolutionized this mutation discovery process by allowing rapid identification of the homozygous nucleotide change present in all affected family members. Mutations in seven genes, MEGF10, ISPD, KLHL40, TRAPPC11, HACD1, KLHL41, MICU1, were identified using this approach (see Table 3 for muscle disorders caused by mutations in these genes) [15,21,[24][25][26][27][28]. In several cases of dominant myopathies, the list of candidate genes was narrowed down using genome-wide linkage analysis and subjected to massively parallel sequencing.…”
Section: Discovery Of Novel Genes Implicated In Myopathies Using Massmentioning
confidence: 99%
“…There are three TRAPP complexes that share a core of seven subunits and contain additional subunits that give their specific functions (figure 1A): 1) TRAPP I regulates vesicle trafficking from the ER to early Golgi; 2) TRAPP II controls intra-Golgi trafficking and 3) TRAPP III is required for autophagy 1. Mutations in TRAPP subunits have been associated with several human diseases, ranging from spondyloepiphyseal dysplasia tarda (TrappC2 (MIM 300202); adaptor),2 limb girdle muscular dystrophy (TrappC11 (MIM 614138); TRAPP III)3 and intellectual disability with microcephaly (TrappC9 (MIM 611966); TRAPP II) 4. However, how mutations in different TRAPP subunits lead to such diverse clinical phenotypes remains unclear.…”
Section: Introductionmentioning
confidence: 99%